Liver Perfusion Changes Occurring During Pancreatic Islet Engraftment: A Dynamic Contrast‐Enhanced Magnetic Resonance Study. Issue 1 (12th November 2013) - Esposito, A.; Palmisano, A.; Maffi, P.; Malosio, M. L.; Nano, R.; Canu, T.; De Cobelli, F.; Piemonti, L.; Ironi, G.; Secchi, A.; Del Maschio, A.
Abstract The aim of this study was to investigate liver microvascular adaptation following the intraportal infusion of pancreatic islets (pancreatic islet transplantation [islet‐tx]) in diabetic patients using dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI). DCE‐MRI was performed before and 7 days after islet‐tx in six diabetic patients. Initial area under curve (AUC60) and volume transfer coefficient (Ktrans) were assessed as markers of liver perfusion. Clinical and metabolic monthly follow‐up was performed in all patients, considering fasting C‐peptide and β‐score as main indices of graft function. High variability in the response of liver microvasculature to islet infusion was observed: two patients showed a significant reduction in liver perfusion after transplantation (pt.2: AUC60 = −23.4%, Ktrans = −31.7%; pt.4: AUC60 = −23.7%, Ktrans = −27.9%); three patients did not show any significant variation of liver perfusion and one patient showed a significant increase (pt.3: AUC60 = +31%, Ktrans = +42.8%). Interestingly, a correlation between DCE‐MRI parameters and indices of graft function was observed and, in particular, both patients with DCE‐MRI evidence of posttransplantation liver perfusion reduction experienced premature graft failure. Our preliminary study demonstrated that DCE‐MRI may identify different adaptive responses of liver microvasculature in patients submitted to islet‐tx. These different responses could have an impact on islet engraftment, although reported findings need confirmation from larger studies.